Pendampingan Penyusunan Media Pembelajaran Digibook (Buku Digital) di SDN Girimoyo 2 Kabupaten Malang - Erna Yayuk; Kuncahyono Kuncahyono; Arina Restian (Prodi PGSD FIP UNM, 2017)
Digibook is a digital book that has access to information, has facilities that can make learning more interesting, visual and interactive. This activity involves cooperation with the partner schools SDN Girimoyo 2 Malang Regency. To succeed in this partnership teachers who will become trainees need to get strengthened concepts, learning media materials, and new experiences in developing technology-based media as a support in conducting classroom learning activities optimally.The method of implementation in this activity is training workshop, mentoring, and implementation digibook media. Further activities of assistance is making digibook (digital book). Assistance is done in order to manufacture media digibook product (digital book). Each teacher will get direct mentoring from the team. In this mentoring activities teachers are accompanied so that teachers are directly able to produce digibook (digital book) products in accordance with the material being taught.The final result showed as a form of finishing from making media digibook that is media product digibook and implementation media digibook (digital book) on learning. Teachers can implement digibook products (digital books) that have been made in the previous stage and realized in the learning activities. The companion team acts as an observer who will observe and provide resolutions regarding the application of media digibooks (digital book) to classroom learning.